Pectins, hemicellulose and lignocellulose profiles vary in leaves among different aromatic Vanilla species (Orchidaceae) - Warner Pineda, Jorge (2023)
The alcohol-insoluble residue in Vanilla dressleri, V. odorata, V. planifolia and V. pompona mature leaves was fractionated into water-, oxalate-, HCl- and NaOH-soluble pectins, hemicellulose and lignocellulose. Neutral sugars and uronic acids of each fraction were determined by high-performance anion exchange chromatography pulsed amperometric detection. V. dressleri differentiated from the other three species based on the higher amounts of the HCl-soluble pectin fraction and the amount of glucose exceeding 5–7 times the values found in the NaOH-soluble pectin fraction in the other species, as well as a cellulose/hemicellulose ratio of ca. 2/3. Analogously, V. planifolia could also be distinguished by its higher cellulose/hemicellulose ratio of ca. 7. In addition to taxonomical implications, these results might be instrumental for defining adequate conditions for cell wall digestion aiming at protoplast isolation and appropriate media composition for cell wall regeneration during protoplast culture, which has been elusive in the Orchidaceae.